2023
DOI: 10.1111/1744-7917.13269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pyrethroid and organophosphate insecticides on reared black soldier fly larvae (Hermetia illucens)

Nathan Meijer,
Lisa Zoet,
Theo de Rijk
et al.

Abstract: Black soldier fly larvae (Hermetia illucens) receive growing interest as a potential alternative animal feed source. These insects may be exposed to insecticide residues in the rearing substrate. This study aimed to investigate the effects of six different pyrethroid and organophosphate insecticides on this insect species’ performance. The toxicity of two “model” substances for each of these classes (cypermethrin; pirimiphos‐methyl) was quantified, with and without the synergist piperonyl butoxide (PBO). Criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Furthermore, elevated transfer from substrate to larvae was observed for cypermethrin (30.8%), deltamethrin (26.3%), and permethrin (26.4%) when a cocktail of these substances was used in conjunction with PBO than without it (12.8, 10.4, 8.3%, respectively). This suggested that elevated mortality and reduced yield were correlated with higher transfer of pesticides to the larval biomass, and that this was mediated by the presence of PBO (Meijer et al, 2023). The latter would be in line with the intended effect of PBO to block the detoxifying capacity of cytochrome P450 enzymes (Snoeck et al, 2017).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Furthermore, elevated transfer from substrate to larvae was observed for cypermethrin (30.8%), deltamethrin (26.3%), and permethrin (26.4%) when a cocktail of these substances was used in conjunction with PBO than without it (12.8, 10.4, 8.3%, respectively). This suggested that elevated mortality and reduced yield were correlated with higher transfer of pesticides to the larval biomass, and that this was mediated by the presence of PBO (Meijer et al, 2023). The latter would be in line with the intended effect of PBO to block the detoxifying capacity of cytochrome P450 enzymes (Snoeck et al, 2017).…”
Section: Introductionmentioning
confidence: 77%
“…A concentration/response curve was calculated for deltamethrin. Data for cypermethrin was compared to the curve calculated in Meijer et al (2023). The substrate (pre-trial) and selected larvae and frass samples (post-trial) were analysed using liquid chromatography tandem mass spectrometry (LC-MS/MS) to determine concentrations of the primary compounds.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another found that λ-cyhalothrin negatively affected BSFL development but was nonetheless degraded in the substrate and not bioaccumulated [ 66 ]. Others found that while spinosad, deltamethrin, and cypermethrin present in a substrate at the EU’s maximum residue level negatively affected BSFL growth, imidacloprid stimulated growth while chlorpyrifos, propoxur, and tebufenozide had no effect even at ten times the maximum residue level [ 64 , 67 ]. Toxicity increased if multiple compounds were in the substrate at the same time, or if synergists like piperonyl butoxide were added.…”
Section: Introductionmentioning
confidence: 99%